From multi-omics to functional validation: the PTMRS stratifies TME and positions PDGFRB in CRC biology - Liu, Yanhong; Lu, Chao; Hua, Luchun; Hao, Hankun; Zhang, Qijing; Zou, Zongyou; Xiang, Jianbin; Wang, Yaping (Frontiers in Immunology, 2026)
BackgroundColorectal cancer (CRC) outcomes remain heterogeneous despite therapeutic advances, posing challenges to precise prognostic stratification. Post-translational modifications (PTMs) critically regulate protein function, tumor microenvironment (TME) crosstalk, and CRC progression, while most existing studies only focus on single PTM types and PTM signals are rarely integrated into CRC risk models.MethodsWe built a post-translational modification–related risk signature (PTMRS) model by screening post-translational modification–related (PTM-related) genes associated with prognosis in The Cancer Genome Atlas (TCGA) and Genotype-Tissue Expression project (GTEx)datasets, then benchmarking 101 modeling strategies to select a Cox partial least squares framework. External validation was conducted across multiple independent cohorts and immunotherapy datasets. Single-cell RNA sequencing (scRNA-seq) data were used to calculate cell type–specific scores for the PTMRS and to perform CellChat-based analyses of cell–cell communication. To investigate mechanism, we targeted platelet-derived growth factor receptor-β (PDGFRβ) in human colonic fibroblasts and assessed CRC-cell responses to their conditioned media.ResultsPTMRS robustly stratified overall survival across cohorts and aligned with an immune-cold, stroma-enriched phenotype. PTMRS was associated with pathways related to antigen presentation, protein homeostasis, and other processes within the CRC TIME. ScRNA-seq analysis further showed that PTMRS scores influenced intercellular communication between CRC cells and immune cells. PDGFRB was validated as a core node within the PTMRS network: activation of PDGFRβ in human colonic fibroblasts promoted CRC cell proliferation and migration, whereas sunitinib attenuated and reversed these effects.ConclusionsWe established a post-translational modification–related risk signature (PTMRS) that robustly stratifies CRC prognosis and links tumor-intrinsic programs with features of the TIME. Higher PTMRS scores, particularly in tumors with PDGFRB enrichment, were associated with a stroma-rich, immune-cold phenotype. Experimental validation highlighted PDGFRβ in colonic fibroblasts as a stromal hub whose activation promotes CRC cell proliferation and migration. These findings suggest that PTMRS may help identify patients who could benefit from combining immunotherapy with therapies targeting PDGFRβ or other PTM-related pathways. Further validation in in vivo models and prospective clinical cohorts is needed.